(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The same qualities of many platforms offer excellent solutions for small and medium-sized businesses as FinTech continues to expand. This study investigates if FinTech provides practical business tools for SMEs in particular ASIAN nations. Indonesia, Malaysia, Philippines, Singapore, and Thailand are the ASIAN nations included by the research. The study divided the FinTech-SME nexus into five variables using factor analysis. Surveys and interview questionnaires were used to get the opinions of 300 SME owners. According to our research, the COVID-19 new FinTech and SMEs "collisions" (our name for new use) are the key drivers of FinTech development and SMEs’ resilience. Additionally, we used the Kruskal-Wallis test to confirm our findings and rank the variables in comparison to the ASIAN nations. We offer practical recommendations for accepting FinTech technologies to ease digital transactions for policymakers, regulatory organizations, ASIAN nations, and SMEs.